Smart Room Service Apps / Seomgyeol Lee ... [et al.] - Seomgyeol, Lee; Mohd Zuhaimi, Nur Afiqah; Ahmad Amizan, Ahmad Fawwas; Abdul Kepli, Nurul Ain; Shahidan, Shafira (2022)
As a result of confinement-related difficulties, the COVID-19 pandemic has caused radical changes in tourism industry. The purpose of this project is to design a system for a hospitality service that can be used by the Telecommunication industries that are affected by the COVID 19 in its daily promotion.